2021
DOI: 10.3390/mi12111385
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Transportation through an Orifice on Electrode for Digital Microfluidics Modulations

Abstract: A digital microfluidic modular interface (chip-to-chip interface) which possesses an electrode with an orifice to vertically transport core–shell droplets is presented. The electrodes were geometrically designed to promote droplet deformation and suspension. The droplets were then applied with an electrical potential for insertion into and passage through the orifice. The concepts were tested with three types of droplets at the volume of 0.75~1.5 μL, which is usually difficult to transfer through an orifice. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Not only can this 3D EWOD technology allow larger volumetric capacities, but it can also provide much more flexibility and functionality than two-dimensional (2D) planar devices. Relevant studies of 3D EWOD technology have been widely demonstrated, including droplet actuation on uneven terrains, [82][83][84] vertical translation, [85][86][87][88] droplet jumping, [89][90][91][92] even in the form of wearable wristbands for portable point-of-care (POC) applications, 93,94 and new fabrication methods of 3D devices. [95][96][97] Despite such numerous studies on 3D EWOD technology, it was challenging for OEW researchers to demonstrate light-driven 3D droplet manipulations on flexible substrates due to the incompatibility of depositing photoconductive materials that have been commonly used for previous OEW devices onto flexible substrates.…”
Section: Flexible Scoew Device For 3d Droplet Manipulationmentioning
confidence: 99%
“…Not only can this 3D EWOD technology allow larger volumetric capacities, but it can also provide much more flexibility and functionality than two-dimensional (2D) planar devices. Relevant studies of 3D EWOD technology have been widely demonstrated, including droplet actuation on uneven terrains, [82][83][84] vertical translation, [85][86][87][88] droplet jumping, [89][90][91][92] even in the form of wearable wristbands for portable point-of-care (POC) applications, 93,94 and new fabrication methods of 3D devices. [95][96][97] Despite such numerous studies on 3D EWOD technology, it was challenging for OEW researchers to demonstrate light-driven 3D droplet manipulations on flexible substrates due to the incompatibility of depositing photoconductive materials that have been commonly used for previous OEW devices onto flexible substrates.…”
Section: Flexible Scoew Device For 3d Droplet Manipulationmentioning
confidence: 99%
“…Although the use of a femtosecond laser can provide a higher resolution down to the sub-micro level, it can spend hours fabricating a single chip and significantly increases the cost. Several related works have focused on developing an orifice-based ITO-DMF chip [ 22 ] and investigating the surface wettability and electrical resistance of ITO glass to improve the droplet control [ 23 ]. There is still a lack of studies focusing on droplet deformation induced by lead wire.…”
Section: Introductionmentioning
confidence: 99%